Kelayakan Finansial pada Usaha Pengolahan Abon Ikan Skala Rumah Tangga di Kawasan Konservasi TWP Gili Matra, Kabupaten Lombok Utara - Soraya Gigentika; Sitti Hilyana (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The large potential of fish resources and human resources in Gili Matra TWP is one of the opportunities that can be utilized by fish processing community groups in Gili Matra TWP. One of the fish processing groups in Gili Matra TWP is the Putri Bahari group which carries out business activities of processing shredded fish. In this study, a business feasibility study and investment feasibility will be carried out in a household-scale shredded fish processing business carried out by the Putri Bahari Group in the Gili Matra TWP area. Data collection in this study was carried out in Gili Air Hamlet, where the respondents were members of the Putri Bahari Group and fishermen in Gili Air Hamlet. Data analysis conducted in this study consisted of descriptive analysis, business analysis, and investment analysis. The results obtained in this study indicate that the fish floss processing business carried out by the Putri Bahari fish processing group is feasible to be carried out in the short term (for 1 year) and in the long term (for 15 years). Fish floss production activities will be carried out 2 times a week for 5 months during the medium fish season and 3 times a week for 5 months during the fish season. The net profit obtained from the shredded fish processing business is Rp 46,352,500. The results showed that the shredded fish processing business in TWP Gili Matra had an R/C value of 2.11; ROI value of 371.86%; PP value of 0.27 years or 3.23 months; NPV value of Rp 30,681,818; IRR value of 15.18%; and the Net B/C value of 15.77.